Study on the Corrosion Failure Mechanism and Integrity Management Strategies of Flash Evaporation Heat Exchanger - WANG Chuanping, LYU Xiaoming, ZHANG Hongjie, LIU Junlin, PENG Wanli, LIU Mingming, ZHONG Xiaolin, TONG Xubo (Cailiao Baohu, 2024)
The corrosion and perforation failure of the flash evaporation heat exchanger tube bundle in a certain treatment station occurred frequently. Therefore, a composition test was conducted on the external media and corrosion products on the surface of the tube bundle. Results showed that the condensate oil medium in the shell side contained a small amount of water, and there were the high concentrations of Cl-, Ca2+ and HCO3- in the water quality components. A black scale layer was formed on the surface of the tube bundle, with patches of corrosion pits under the scale, indicating severe local corrosion. Based on the analysis of the morphology, elements and compounds of the corrosion products, it was found that the corrosion products were mainly composed of FeCO3, and a chlorine-rich layer was formed on the surface of the tube bundle. Therefore, a corrosion mechanism of synergistic HCO3- and Cl- under scale was established. Finally, an integrity management process for flash evaporation heat exchangers with failure control as the core was established, and targeted risk assessment methods and failure control measures were formed to provide assurance for the safe production of the treatment station.